Efficacy of a new comprehensive method of treatment for bacterial keratitis (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the therapeutic efficacy of hyperbaric oxygenation (HBO) therapy and liposomal ozone-based solution (LOBS) in the comprehensive treatment of bacterial keratitis (BK).Material and Methods: Ninety-eight patients (98 eyes) were treated for BK and the treatment outcomes were studied. Histories and complaints were thoroughly taken and patients underwent  microbiological examination and comprehensive eye examination including visual acuity, refractomerty, pneumotonometry, biomicroscopy, fluorescein staining assessment of corneal re-epithelaliization, ophthalmoscopy, ultrasound B-scanning, and anterior-segment optical coherence tomography at admission, treatment day 10 and at one month. Patients were randomly divided into 3 clinical groups: a control group (32 patients, 32 eyes), group 1 (33 patients, 33 eyes) and group 2 (33 patients, 33 eyes). Groups were statistically comparable in terms of the number of patients, age and gender. In all three groups of patients, treatment included antiseptic (miramistin 0.1 mg/ml), antibiotics (ciprofloxacin 0.3% and tobramycin 0.3% until results of microbiological cultures became available; the most sensitive antibiotic was selected based on the results of bacterial culture), mydriatic (cyclopentolate), tear substitute with reparing agent (dexpanthenol 2% and sodium hyaluronate 0.15), and antibiotic administered parabulbarly (amikacin, 0.5 ml). In addition, patients in groups 1 and 2 were administered ten 45-minute sessions of hyperbaric 95-percent medical oxygen at 1.5 atmospheres. Moreover, patients in group 2 were administered topical LOBS.Results: In group 2, inflammation attenuation was faster, and there was a reduction in the time to resolution of infiltration by 5.9 ± 0.2 days compared to the control group and by 2.7 ± 0.2 days compared to group 1. In groups 2 and 1, corneal re-epithelaliization completed 8.2 ± 0.2 days and 4.8 ± 0.2 days earlier, respectively, than in the control group (p < 0.001). In group 2, there was a reduction in the length of inpatient stay at the hospital of 6.6 ± 0.2 days compared to the control group and of 3.4 ± 0.2 days compared to group 1 (р < 0.001).Conclusion: HBO therapy plus LOBS, when used as adjuncts to conventional treatment for BK, resulted in significantly faster inflammation attenuation and reduced time to resolution of infiltration, time to corneal re-epithelaliization, and length of in-patient stay at the hospital. Therefore, the new method of treatment for BK was found therapeutically effective and can be recommended for application in clinical practice.
Keywords: bacterial keratitis; inflammation; treatment; hyperbaric oxygenation; liposomal ozone-based solution; cornea